Assessing the role of Persistent Organic Pollutants (POPs) in cancer development in Nigeria: environmental exposure, risk factors, and policy gaps - Daniel Omeodisemi Omokpariola; Patrick Leonard Omokpariola; Victor Uchenna Okechukwu; Abuchi Princewill Okeke; Anu Adekunle Daramola (Discover Toxicology)
Abstract Persistent Organic Pollutants (POPs) are toxic chemicals that resist environmental degradation and accumulate in ecosystems, posing long-term health risks globally to aquatic lives, human health and the environment. In Nigeria, their prevalence is amplified by industrialization and inadequate waste management. This research delves into the significant role of Persistent Organic Pollutants (POPs) in the development of cancer, focusing on Nigeria's environmental exposure, risk factors, and policy gaps. POPs released from industrial chemicals, and combustion byproducts, are recognized for their toxic and carcinogenic effects. Despite international and localized efforts, exposure to POPs remains a significant concern, particularly in Nigeria, affected by oil spills, gas flaring, electronic waste and pesticide use that makes up anthropogenic releases. The study reviews environmental pollutants linked to cancer, their pathways through food and water, and epidemiological evidence of cancer related to chemical exposure. The challenges which are data collection issues, underreporting, and inadequate health surveillance hinder establishing clear causality between POPs and cancer rates. The vulnerable populations, especially in rural and urban slum areas, face disproportionate exposure due to inadequate environmental protection, lack of awareness, and low socioeconomic status. These disparities worsen health outcomes, with poorer populations having less access to medical care and protective measures. The policy landscape reveals significant gaps in regulating and enforcing laws on POPs, with limited implementation due to capacity constraints, lack of political will and public awareness. The review calls for comprehensive policy reforms, better enforcement, and strengthened international collaborations to mitigate POPs health impacts. By implementing these measures, Nigeria can reduce exposure to harmful chemicals and mitigate associated health risks, moving towards a healthier, more sustainable future. Graphical Abstract